Inspecting inspection reports, does the type of restaurant change the risk? - Cseke, Paul; BCIT School of Health Sciences, Environmental Health; Heacock, Helen; Sidhu, Bobby; McIntyre, Lorraine; Wilcott, Lynn (BCIT Environmental Public Health Journal, 2014)
Background An estimated of 4 million Canadians (one in eight people) become ill every year from a food-borne illness (Thomas et al., 2013). The economic and social burdens of these illnesses are vast. As restaurants are a big sector of the food industry, improving their food safety would reduce the risk of food-borne illnesses. Environmental Health Officers (EHOs) are on the front line, educating restaurant operators in order to improve food safety. In Metro Vancouver there are many different types of ethnicities and types of restaurants; this provides a challenge for EHOs to know where to allocate their time and resources. Methods The author analyzed 150 Fraser Health inspection reports in the Burnaby, New Westminster and Surrey municipalities. The restaurants fell into three different categories: i) Independently owned ethnic, ii) Independently owned, non-ethnic and iii) chain non-ethnic restaurants. Hazard ratings, number of critical and number of non-critical violations from their latest inspection report were compared. Each violation code was also recorded to identify any infraction trends that exist. Results Analysis of the number of critical violations identified ethnic, chain non-ethnic, and independent non-ethnic restaurants as not being significantly different (p=0.09). The number of non-critical violations was different (0.033), with ethnic restaurants having the most. The number of critical violations, when treating each ethnicity as its own category, is however significantly different (p=0.044) between restaurant types. There was a significant association between hazard rating and restaurant type, with independent ethnic restaurants having the worst hazard rating (p=0.017). Conclusion The type of ownership (independent vs chain) and the restaurant type were not a factor when looking at number of critical violations that a restaurant commits. Independent ethnic restaurants had a slightly higher mean number of critical violations. Japanese restaurants had the highest number of critical violations out of the three ethnicities studied. These findings suggest a slight disparity in risk to public health between ethnic and non-ethnic restaurants.